Adaptation of a Blended Method for Various Learning Styles to Enhance Competence in the Educational Domain - Sheshasaayee, Ananthi; Malathi, S (International Journal of Computer Sciences and Engineering, 2025)
Learning is a combined factor in education. Individual learning styles differs from each student to student. The very term “learning styles” means, the method of understanding the students learning behavioural pattern. As not all student learns the same way the methods of observing, absorbing the concept, the methods of implementing the read facts and the memory of retaining the learned information differ from individual to individual. Every single student learns in their own perceptive way and not all students learn and understand the same way. Individual learning of concept depends on various factors such as cognitive factor, environmental factor, experimental factor as well as emotional factor and so do the styles also depend upon instructional design, individual behaviour, need to master the concept, e-materials, other digital resources and teaching guidance. Each individual follow a different processes and categorizes information differently based on personal requirements. The ways of social interaction also differs from person to person. In this paper the varied learning styles along with blended methods which, is the combination of both classical and non-classical education programs are well discussed towards competence enhancement benefitting the educational domain.